Development of TanDEM-X DEM Calibration Concept - Hueso-Gonzalez, Jaime; Bachmann, Markus; Fiedler, Hauke; Huber, Sigurd; Krieger, Gerhard; Wessel, Birgit; Zink, Manfred (European Radar Conference (EuRAD), 2007)
The TanDEM-X mission [1] comprises two fully active synthetic aperture radar satellites operating in X-band. The primary goal of this mission is the derivation of a high-precision global Digital Elevation Model (DEM) according to HRTI level quality [2]. This requires accurate calibration of the interferometric system parameters, where the interferometric height is determined by the phase difference between the two images and the spatial geometry. Content of this paper is the development of a general concept for this calibration, which has a key incidence on mission aspects like the data acquisition plan and the data take adjustment and mosaicing. © 2007 EuMA.
DLR Import::2019-04-03